Dampak Pemilihan Lokasi terhadap Arsitektur Bangunan Benteng Karang Bolong di Pulau Nusakambangan - Suciningrum, Putri Rizqi; Bawono, Rochtri Agung; Kristiawan, Kristiawan (Humanis; Vol 26 No 2 (2022)DO - 10.24843/JH.2022.v26.i02.p14, 2022)
This article discusses the impact of site selection on the architecture of the Karang Bolong Fort. Data collection was done by using observation, interviews, and literature studies techniques. The research uses the analysis techniques of the outside of the buildings and qualitative analysis. The supporting theory used is the theory of landscape architecture. The results of this study provide an overview of site selection of Karang Bolong Fortress which affect the architecture form of the fort. Seeing the location, the Dutch East Indies government chose to adapt the Napoleon Tower model with some adjustments in the function and number of rooms. The architectural shape of the defense tower was chosen because it is in accordance with the function of Karang Bolong Fort as a defensive fortress on the east coast of Nusakambangan Island.